2022
DOI: 10.3389/fonc.2022.899170
|View full text |Cite
|
Sign up to set email alerts
|

Immune Activation, Exhaustion and Senescence Profiles as Possible Predictors of Cancer in Liver Transplanted Patients

Abstract: Liver transplanted (LT) patients for hepatocellular carcinoma (LT-HCC) or for other causes (LT-no-HCC) may develop post-transplantation malignancies. Although immune activation and senescence are frequently implicated in cancer development, no data is available on their possible role as biomarkers predictive of tumor onset in this setting. A total of 116 patients were investigated: the 45 LT-HCC patients were older than the 71 LT-non-HCC (p=0.011), but comparable for sex, HCV, HBV infection and immunosuppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The authors demonstrated that the mRNA expression of EZH2, G6PD, LGALS3, and PSMD14 senescence-related genes was elevated in cancer tissues from HCC patients compared with normal gastric cancer parietal tissues, suggesting that these genes may act as potential biomolecular markers for the prognosis and stratification of HCC patients. Similarly, immune senescence profiles have been shown to possibly predict HCC prognosis in liver transplant patients [128]. Overall, the realization of a prognostic model for cellular senescence risk score can not only be exploited to predict HCC patients' prognosis, but can also provide more strategies for the clinical treatment of HCC patients.…”
Section: Senescence In Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…The authors demonstrated that the mRNA expression of EZH2, G6PD, LGALS3, and PSMD14 senescence-related genes was elevated in cancer tissues from HCC patients compared with normal gastric cancer parietal tissues, suggesting that these genes may act as potential biomolecular markers for the prognosis and stratification of HCC patients. Similarly, immune senescence profiles have been shown to possibly predict HCC prognosis in liver transplant patients [128]. Overall, the realization of a prognostic model for cellular senescence risk score can not only be exploited to predict HCC patients' prognosis, but can also provide more strategies for the clinical treatment of HCC patients.…”
Section: Senescence In Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…Approximately three-quarters to four-fifths of patients diagnosed with primary liver cancer have HCC. Characterized by rapid progression, high metastasis potential, and late diagnosis at advanced stages, HCC often has a poor prognosis due to high recurrence rates after surgery or other treatments ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…potential, and late diagnosis at advanced stages, HCC often has a poor prognosis due to high recurrence rates after surgery or other treatments (5).…”
mentioning
confidence: 99%